GE_GERICHTE P/6925/2024 vom 10. Juni 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;LÉSION CORPORELLE SIMPLE;ABUS D'AUTORITÉ;POLICE;ARRESTATION;PROPORTIONNALITÉ | CPP.310; CPP.217; CPP.200; CP.312; CP.123; CP.14